Hollow nanoflower NiCo-LDH and preparation method and application thereof

By synthesizing hollow nanoflower NiCo-LDH with DMSO on the ZIF-67 template, the problem of reduced effective specific surface area and poor electrochemical performance caused by the nanosheet-like structure of existing electrode materials is solved, and higher specific capacitance and electrochemical performance are achieved.

CN119724941AActive Publication Date: 2025-03-28GUILIN UNIV OF ELECTRONIC TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411835403.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Among the existing supercapacitor electrode materials, metal hydroxides tend to form nanosheet-like structures, resulting in a decrease in effective specific surface area and poor electrochemical performance, which limits its application effect.

Method used

NiCo-LDH was synthesized by using the polar organic solvent DMSO on the ZIF-67 template and etched and grown by nitrate, making it a hollow nanoflower structure with a secondary structure on the wall, exposing more active sites and shortening the electron transport path.

Benefits of technology

A larger specific surface area and better electrochemical performance are achieved, and the specific capacitance of the supercapacitor is improved, reaching 1538-1834F g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724941A_ABST
    Figure CN119724941A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow nanoflower NiCo-LDH, which is characterized in that nickel nitrate, cobalt nitrate, dimethylimidazole, dimethyl sulfoxide and hexadecyl trimethyl ammonium bromide are used as raw materials, deionized water and absolute ethyl alcohol are used as solvents, the NiCo-LDH is synthesized through a precipitation method and a hydrothermal method, and the NiCo-LDH is of a hollow nanoflower structure; the size of the hollow nanoflower NiCo-LDH is 600-700 nm, the wall of the hollow nanoflower structure has a secondary structure, the secondary structure is a layered structure formed by small hydrangea, the size of the small hydrangea is 100 nm, and the primary unit of the small hydrangea is an LDH sheet. The preparation method comprises the following steps: 1, preparing ZIF-67; and 2, preparation of the hollow nano flower NiCo-LDH. When the HNF-NiCo-LDH-6 / NiCo-LDH-6 composite material is used as a supercapacitor electrode material, the specific capacitance of the HNF-NiCo-LDH-6 is 1538-1834F g <-1 > when the discharge current density is 1A g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a hollow nanoflower NiCo-LDH and a preparation method and application thereof. Background Art

[0002] Supercapacitors have high power density and can achieve rapid charge and discharge in a short time. Pseudocapacitors can store electrical energy through fast and reversible Faradaic redox reactions on the electrode surface, so in theory pseudocapacitor materials have high capacitance. Among them, transition metal hydroxides are a type of supercapacitor electrode material with high theoretical capacity. However, the metal hydroxides actually prepared at present tend to generate nanosheet structures. The aggregation of this structure reduces the effective specific surface area of ​​LDHs, further limiting the electrochemical performance. As a result, the actual specific capacitance is much lower than the theoretical specific capacitance, which greatly limits their application effect in the field of supercapacitors.

[0003] There are three common solutions:

[0004] 1. Adjust the morphology by compounding with carbon-based materials. For example, the existing literature 1 (Chen S, Zhang Y, Zhang, H, et al. The flower-like BSC / NiCo-LDHs composite as a high-performance active material for flexible supercapacitors) uses biomass porous carbon and nickel cobalt hydroxide to synthesize nano-flower-like BSC / NiCo-LDHs materials. -1 974F g -1 Although this technical solution obtains a larger specific surface area than a sheet structure by preparing nanoflowers, the irregular microscopic morphology of the carbon material used leads to uneven sizes of the obtained nanoflowers, among which the nanoflowers with smaller sizes are agglomerated.

[0005] 2. Adjust the morphology by introducing a carrier. For example, the existing literature 2 (Xu L, Li Y, Li M, et al. Mo-doped NiCo-LDH nanoflower derived from ZIF-67 nanosheet arrays for high-performance supercapacitors) loaded NiCo-LDH doped with Mo metal ions on carbon cloth to synthesize Mo-NiCo-LDH@C nanoflower structure. -1 The following has 1368.4C g -1This technical solution achieves the technical effect of adjusting the electronic structure of NiCo-LDH by introducing an amorphous phase through doping Mo ions, thereby improving the charge storage dynamics. However, the interaction force between NiCo-LDH nanoflowers and carbon cloth is relatively small, which directly leads to the inability of NiCo-LDH nanoflowers to be uniformly loaded on the carbon cloth, and during the cycle, NiCo-LDH nanoflowers fall off from the surface of the carbon cloth.

[0006] 3. By adjusting the preparation method, the flake morphology is adjusted to a core-shell structure. For example, the existing literature 3 (Shi Y, Xue J, Yu Y, et al. Facile construction of Mn2O3@NiMn LDH composites electrode with cube core-shell structures for high performance supercapacitors) uses a chemical precipitation method to in situ grow NiMn-LDH on the surface of MnO2S to synthesize a core-shell structure Mn2O3@NiMn LDH. At a current density of 0.5A -1 The following has 1280F g -1 This technical solution constructs a core-shell structure and uses Mn2O3 as a core structure to inhibit the collapse of the electrode structure and improve the initial specific capacitance of the electrode. However, the size of the core-shell structure obtained by this technical solution is micrometer-level, which leads to a decrease in the electron transfer rate.

[0007] It can be seen from the above existing literature that the microscopic morphology of the composite material has a significant impact on the performance, and although the existing technologies use different technical solutions, they have all successfully adjusted the microscopic morphology of the composite material. Further research found that although the technical problems existing in the existing technical solutions have different manifestations, the common technical problems are that the microscopic morphology of the obtained material is uneven, which leads to the shedding of the active substance after loading, and the large size of the material is not conducive to electron transmission.

[0008] According to the inventors' research, since the metal organic framework material MOF has a specific morphology, it can adjust the microscopic morphology of the composite material when used as a template, thereby solving the above problems; in addition, MOF also has a rich pore structure, which can improve the transmission and storage of electrons. In addition, according to the inventors' research, the technical effect of adjusting the morphology can also be achieved by using solvents with different characteristics, thereby enhancing the interaction between metal ions and organic ligands in the MOF material, thereby having better crystallinity.

[0009] Therefore, the inventors combined the above two methods: adding polar organic solvent DMSO and using ZIF-67 as a template to adjust the micromorphology of NiCo-LDH in order to obtain a larger specific surface area and expose more electrochemical sites. Summary of the invention

[0010] The purpose of the present invention is to provide a hollow nanoflower NiCo-LDH and its preparation method and application. In view of the problems existing in the prior art,

[0011] By using the polar organic solvent dimethyl sulfoxide (DMSO) as a solvent to synthesize ZIF-67, the high polarity of DMSO is utilized to enhance the interaction between metal ions and organic ligands, promote the coordination between the two, and thus improve the crystallinity;

[0012] The template ZIF-67 is then etched and grown with nitrate to make NiCo-LDH a hollow nanoflower. The wall of the hollow nanoflower structure has a secondary structure. The secondary structure is a layered structure composed of small hydrangeas, which is conducive to exposing more active sites, shortening the electron transmission path, and effectively improving its electrochemical performance.

[0013] At the same time, DMSO molecules are embedded in the framework structure of ZIF-67, and then interact with metal ions or reaction intermediates to change the reaction path and energy, making it easier for oxygen vacancies to appear in the material during the synthesis process.

[0014] Therefore, the inventive principle of the present invention can be simply summarized as follows: the transition metal elements have rich valence states and exhibit high Faradaic capacitance during the electrochemical redox reaction; at the same time, the secondary structure is used to improve the stability of the composite material, expose more active sites, shorten the electron migration path, and improve conductivity.

[0015] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0016] A hollow nanoflower NiCo-LDH is prepared by using nickel nitrate, cobalt nitrate, dimethylimidazole, dimethyl sulfoxide and hexadecyltrimethylammonium bromide as raw materials, deionized water and anhydrous ethanol as solvents, and synthesizing the NiCo-LDH through precipitation and hydrothermal methods. The NiCo-LDH is a hollow nanoflower structure. The size of the hollow nanoflower NiCo-LDH is 600-700nm, and the wall of the hollow nanoflower structure has a secondary structure, which is a layered structure composed of small hydrangeas. The size of the small hydrangeas is 100nm, and the primary unit of the small hydrangeas is an LDH flake.

[0017] A method for preparing hollow nanoflower NiCo-LDH comprises the following steps:

[0018] Step 1, preparation of ZIF-67, first, dissolving Co(NO3)·6H2O in deionized water to obtain solution A, and at the same time, dissolving dimethylimidazole 2-MI, thiourea TU, hexadecyltrimethylammonium bromide CTAB and dimethyl sulfoxide DMSO in deionized water to obtain solution B, then mixing solution A and solution B, and reacting by stirring first and then standing, and after the reaction is completed, centrifuging and drying the obtained product to obtain ZIF-67;

[0019] In the step 1, the ratio of Co(NO3)·6H2O, 2-MI, TU, CTAB and DMSO satisfies 8g:17g:1g:0.02g:14mL;

[0020] In step 1, the conditions for stirring first and then standing are: the stirring time is 1 hour and the standing time is 6 hours;

[0021] Step 2, preparation of hollow nanoflower NiCo-LDH, first, under certain conditions, dissolving the ZIF-67 and Ni(NO3)·6H2O obtained in step 1 in anhydrous ethanol and stirring to obtain solution C, then, under certain conditions, subjecting solution C to a hydrothermal reaction, after the reaction is completed, washing and drying the obtained product to obtain hollow nanoflower HNF-NiCo-LDH;

[0022] In the step 2, the mass ratio of ZIF-67 to Ni(NO3)·6H2O is 1:11;

[0023] In step 2, the stirring condition is that the stirring time is 0.5-1h;.

[0024] In step 2, the hydrothermal conditions are: the hydrothermal temperature is 80° C. and the hydrothermal time is 6 hours.

[0025] When the hollow nanoflower NiCo-LDH is used as a supercapacitor electrode material, the discharge current density is 1A. -1 When the specific capacitance of HNF-NiCo-LDH-6 is 1538-1834 F g -1 .

[0026] The beneficial technical effects of the NiCo-LDH material obtained by the present invention were tested experimentally, and the results are as follows:

[0027] XRD test shows that NiCo-LDH has characteristic peaks of NiCo-LDH. The test results show that the composition of NiCo-LDH is NiCo-LDH;

[0028] XPS test shows that NiCo-LDH is composed of Ni, Co, C, N and O, among which Ni exists in +2 valence and Co exists in +2 and +3 valence. Oxygen vacancies also exist, with a content of 32.7%-41.1%;

[0029] According to SEM test, NiCo-LDH is a hollow nanoflower structure with a size of 600-700nm. The wall of the hollow nanoflower structure has a secondary structure, which is a layered structure composed of multiple small hydrangeas. The size of the small hydrangeas is 100nm. The primary unit of the small hydrangea is LDH flakes, which are formed by Ni ion etching and LDH growth.

[0030] TEM and EDS tests show that Ni, Co and O are evenly distributed in the outer layer of NiCo-LDH, and these three elements are not detected in the inner layer. The test results show that NiCo-LDH is a hollow structure. Combining the SEM test and TEM test results, it can be seen that NiCo-LDH is a hollow nanoflower structure.

[0031] After CV test, there is a set of symmetrical redox peaks in the CV curve, indicating that NiCo-LDH has good charge and discharge reversibility. The CV curve profile remains basically unchanged at different scan rates, indicating that NiCo-LDH has good electrochemical stability.

[0032] After three-electrode charge and discharge test, at a discharge current density of 1A -1 When the specific capacitance of NiCo-LDH is 1538-1834 F g -1 .

[0033] Therefore, the hollow nanoflower NiCo-LDH of the present invention has the following advantages over the prior art:

[0034] 1. The NiCo-LDH obtained by the present invention has a hollow nanoflower structure, and the wall of the hollow nanoflower structure has a secondary structure, and the secondary structure is a layered structure composed of small hydrangeas;

[0035] 2. DMSO has extremely high specificity, which can enhance the interaction between cobalt ions and organic ligand dimethylimidazole, promote the coordination between the two, and improve crystallinity and regularity. At the same time, DMSO molecules are embedded in the framework structure of ZIF-67, and then interact with metal ions or reaction intermediates to change the reaction path and energy, making it easier for oxygen vacancies to appear in the material during the synthesis process;

[0036] 3. The electrode material of the present invention has low temperature requirements, short preparation time, economy and simple method for preparation, excellent product performance, and reduced process energy consumption and equipment requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 XRD test patterns of ZIF-67, HNF-NiCo-LDH-6, HNF-NiCo-LDH-3 and HNF-NiCo-LDH-9 materials prepared in Example 1, Comparative Example 2 and Comparative Example 3;

[0038] Figure 2 This is the XPS graph of the HNF-NiCo-LDH-6 material prepared in Example 1;

[0039] Figure 3 This is the SEM image of the HNF-NiCo-LDH-6 material prepared in Example 1;

[0040] Figure 4 TEM image of the HNF-NiCo-LDH-6 material prepared in Example 1;

[0041] Figure 5 This is the EDS image of the HNF-NiCo-LDH-6 material prepared in Example 1;

[0042] Figure 6 The cyclic voltammetry curves of the HNF-NiCo-LDH-6 material prepared in Example 1 at scan rates of 1mV, 2mV, 5mV, 8mV, and 10mV;

[0043] Figure 7 The HNF-NiCo-LDH-6 material prepared in Example 1 was heated to 1Ag -1 Constant current charge and discharge curves under current density;

[0044] Figure 8 This is the SEM image of the HNF-NiCo-LDH-FS material prepared in Comparative Example 1;

[0045] Fig. 9 The ZIF-67, HNF-NiCo-LDH-6, HNF-NiCo-LDH-3 and HNF-NiCo-LDH-9 materials of Example 1, Comparative Example 2 and Comparative Example 3 were heated to 1Ag. -1 Constant current charge and discharge curves under current density;

[0046] Fig.10 This is the SEM image of the HNF-NiCo-LDH-3 material prepared in Comparative Example 2;

[0047] Fig.11 This is the SEM image of the HNF-NiCo-LDH-9 material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0048] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0049] Example 1

[0050] A method for preparing hollow nanoflower NiCo-LDH comprises the following steps:

[0051] Step 1, preparation of ZIF-67, first, dissolve 2.6g Co(NO3)·6H2O in 10mL deionized water to obtain solution A, and at the same time, dissolve 5.2g dimethylimidazole 2-MI, 0.3g thiourea TU, 0.006g hexadecyltrimethylammonium bromide CTAB and 8mL dimethyl sulfoxide DMSO in 102mL deionized water to obtain solution B, then, mix solution A and solution B, and react by stirring first and then standing. After the reaction is completed, centrifuge and dry the obtained product to obtain ZIF-67;

[0052] The conditions of stirring first and then standing still are: stirring time is 1h and standing time is 6h;

[0053] Step 2, preparation of hollow nanoflower NiCo-LDH, first, 0.1g of ZIF-67 obtained in step 1 and 1.16g of Ni(NO3)·6H2O are dissolved in 50mL of anhydrous ethanol and stirred for 1h to obtain solution C, then, solution C is subjected to a hydrothermal reaction at a hydrothermal temperature of 80°C and a hydrothermal time of 6h. After the reaction is completed, the obtained product is washed and dried to obtain hollow nanoflowers Hollow-Nano-Flowers-NiCo-LDH, referred to as HNF-NiCo-LDH. The HNF-NiCo-LDH obtained in specific example 1 is referred to as HNF-NiCo-LDH-6.

[0054] In order to prove the composition and structure of HNF-NiCo-LDH-6, XRD test was carried out. The test results are shown in Figure 1 As shown, HNF-NiCo-LDH-6 has characteristic peaks of NiCo-LDH. The test results show that the component of HNF-NiCo-LDH-6 is NiCo-LDH.

[0055] In order to further prove the elemental chemical valence state of HNF-NiCo-LDH-6, XPS test was performed. The test results are shown in Figure 2 As shown, HNF-NiCo-LDH-6 is composed of Ni, Co, C, N and O elements, among which Ni exists in +2 valence, Co exists in both +2 and +3 valence, and HNF-NiCo-LDH-6 also has oxygen vacancies with a content of 41.1%.

[0056] In order to verify the microstructure of HNF-NiCo-LDH-6, SEM test was performed. The test results are shown in Figure 3 As shown, the microstructure of HNF-NiCo-LDH-6 is a hollow nanoflower structure with a size of 600-700nm. The wall of the hollow nanoflower structure has a secondary structure, and the secondary structure is a layered structure composed of multiple small hydrangeas. The size of the small hydrangeas is 100nm. The primary unit of the small hydrangea is LDH flakes, which are formed by Ni ion etching and LDH growth.

[0057] In order to further verify the microstructure of HNF-NiCo-LDH-6, TEM test and EDS test were carried out. The test results are shown in Figure 4 and Figure 5 As shown, the outer layer of HNF-NiCo-LDH-6 is evenly distributed with Ni, Co and O elements, and these three elements are not detected in the inner layer of HNF-NiCo-LDH-6. The test results show that HNF-NiCo-LDH-6 has a hollow structure. Combining the SEM test and TEM test results, it can be seen that HNF-NiCo-LDH-6 has a hollow nanoflower structure.

[0058] In order to prove the electrochemical performance of HNF-NiCo-LDH-6, HNF-NiCo-LDH-6 was prepared as an electrode. Taking HNF-NiCo-LDH-6 as an example, the specific preparation method of the HNF-NiCo-LDH electrode is as follows: first, 0.008g HNF-NiCo-LDH-6, 0.001g acetylene black, 0.001g polytetrafluoroethylene powder and 0.5mL ethanol are mixed and ground to obtain a mixed material; then, under a pressure of 10kPa, the mixed material is pressed on a 2mm thick nickel foam collector to obtain a electrode; finally, it is dried under air and room temperature to obtain a supercapacitor electrode based on HNF-NiCo-LDH-6. Since there is no need to distinguish, the obtained electrode is also referred to as HNF-NiCo-LDH-6.

[0059] The CV test results of HNF-NiCo-LDH-6 are as follows Figure 6 As shown in the figure, there is a set of symmetrical redox peaks in the CV curve. The test results show that NiCo-LDH-6 is a Faradaic capacitor, and the redox peaks are symmetrical, which means that HNF-NiCo-LDH-6 has good charge and discharge reversibility.

[0060] The CV test results of HNF-NiCo-LDH-6 at different scan rates are shown in Figure 6As shown in the figure, the CV curve profile of HNF-NiCo-LDH-6 at different scan rates remains basically unchanged within the potential window of 0 to 0.6 V. The test results show that HNF-NiCo-LDH-6 has good electrochemical stability.

[0061] The three-electrode charge-discharge test results of HNF-NiCo-LDH-6 are shown in Figure 7 As shown, at a discharge current density of 1Ag -1 When the specific capacitance of HNF-NiCo-LDH-6 is 1834 F g -1 .

[0062] In order to demonstrate the effect of DMSO on NiCo-LDH, Comparative Example 1 is provided, in which NiCo-LDH is prepared without adding DMSO.

[0063] Comparative Example 1

[0064] A method for preparing NiCo-LDH without adding DMSO, wherein step 1 not specifically described is the same as that in Example 1, except that: in step 1, DMSO is not added, and the obtained material NiCo-LDH Flaky structure is referred to as NiCo-LDH-FS.

[0065] In order to prove the composition and structure of NiCo-LDH-FS, XRD test was carried out. The test results are shown in Figure 1 As shown, the diffraction peaks of NiCo-LDH-FS are the same as those of HNF-NiCo-LDH-6, that is, the characteristic peaks of NiCo-LDH also exist. The test results show that NiCo-LDH-FS and HNF-NiCo-LDH-6 have the same composition structure.

[0066] In order to verify the microstructure of NiCo-LDH-FS, SEM test was carried out. The test results are shown in Figure 8 As shown, the microscopic morphology of NiCo-LDH-FS is a sheet structure with a size of 700-800nm, and the sheet structure is formed by the growth and stacking of many irregular nanosheets. Compared with Example 1, it can be seen that the addition of DMSO can transform NiCo-LDH from a two-dimensional sheet structure to a hollow nanoflower structure.

[0067] The charge and discharge test results of NiCo-LDH-FS are shown in Fig. 9 As shown, at a discharge current density of 1Ag -1 When NiCo-LDH-W has a specific capacitance of 1326 F g -1 Compared with Example 1, it can be seen that the addition of DMSO can significantly increase the specific capacitance by 38.3%.

[0068] It can be seen from Example 1 and Comparative Example 1 that the addition of DMSO can transform NiCo-LDH from a two-dimensional sheet structure into a hollow nanoflower structure, which can significantly increase the electrochemical sites; at the same time, adding DMSO and embedding it into the framework structure of ZIF-67 can change the reaction path and energy through interaction with metal ions, which is specifically reflected in that the addition of DMSO can form oxygen vacancies.

[0069] In order to demonstrate the effect of hydrothermal time on NiCo-LDH, Comparative Examples 2 and 3 are provided, in which NiCo-LDH is prepared with hydrothermal time of 3 h and 9 h, respectively.

[0070] Comparative Example 2

[0071] A method for preparing a NiCo-LDH material with a hydrothermal time of 3 hours, wherein step 1 not specifically described is the same as that in Example 1, except that: in step 2, the hydrothermal time is 3 hours, and the obtained material is named HNF-NiCo-LD-3.

[0072] In order to prove the composition and structure of HNF-NiCo-LDH-3 material, XRD test was carried out. The test results are shown in Figure 1 As shown, the HNF-NiCo-LDH-3 material has the characteristic peak of NiCo-LDH. The test results show that the HNF-NiCo-LDH-3 material has the same composition structure as the product HNF-NiCo-LDH-6 of Example 1.

[0073] In order to verify the microstructure of HNF-NiCo-LDH-3, SEM test was performed. The test results are shown in Fig.10 As shown, the microscopic morphology of HNF-NiCo-LDH is a hollow nanoflower structure with a size of 600-700nm, and there are irregular nanosheets on the surface, that is, no small hydrangea structure is etched. Compared with Example 1, increasing the hydrothermal time can promote the etching of Ni ions and the growth of LDH, and further generate a hollow nanoflower structure with a secondary structure, thereby increasing the electrochemical sites.

[0074] In order to prove the electrochemical performance of HNF-NiCo-LDH-3, three-electrode charge-discharge test was carried out. The test results are shown in Fig. 9 As shown, at a discharge current density of 1Ag -1 When HNF-NiCo-LDH-3 has a specific capacitance of 1538 F g -1 Compared with Example 1, it can be seen that increasing the hydrothermal time can increase the specific capacitance by 19.2%.

[0075] Comparative Example 3

[0076] A method for preparing a NiCo-LDH material with a hydrothermal time of 9 hours, wherein step 1 not specifically described is the same as that in Example 1, except that in step 2, the hydrothermal time is 9 hours, and the obtained material is named HNF-NiCo-LD-9.

[0077] In order to prove the composition and structure of HNF-NiCo-LDH-9 material, XRD test was carried out. The test results are shown in Figure 1 As shown, the HNF-NiCo-LDH-9 material has the characteristic peak of NiCo-LDH. The test results show that the HNF-NiCo-LDH-9 material has the same composition structure as the product HNF-NiCo-LDH-6 of Example 1.

[0078] In order to verify the microstructure of HNF-NiCo-LDH-9, SEM test was performed. The test results are shown in Fig.11 As shown, the microscopic morphology of HNF-NiCo-LDH-9 is a nanoflower structure with a size of 700-800nm. Compared with Example 1, further increasing the hydrothermal time directly leads to the self-assembly of NiCo-LDH from the hollow nanoflower structure to the nanoflower structure, which increases in size, and the electrochemical sites of the nanoflower structure are less than those of the hollow nanoflower structure.

[0079] In order to prove the electrochemical performance of HNF-NiCo-LDH-9, three-electrode charge-discharge test was carried out. The test results are shown in Fig. 9 As shown, at a discharge current density of 1Ag -1 When HNF-NiCo-LDH-9 has a specific capacitance of 1630 F g -1 Compared with Example 1, it can be seen that further increasing the hydrothermal time will reduce the specific capacitance by 12.5%.

[0080] By comparing and analyzing Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that the time of the hydrothermal reaction directly determines the microscopic morphology of the composite material, which is specifically reflected as follows:

[0081] 1. When the hydrothermal reaction time is short, due to insufficient etching, the secondary structure of small hydrangeas cannot be formed on the surface of the hollow nanoflower structure, and only irregular nanosheets exist;

[0082] 2. When the hydrothermal reaction time is too long, NiCo-LDH will re-self-assemble.

Claims

1. A hollow nanoflower NiCo-LDH, characterized by: The NiCo-LDH is synthesized by using nickel nitrate, cobalt nitrate, dimethylimidazole, dimethyl sulfoxide and hexadecyltrimethylammonium bromide as raw materials and deionized water and anhydrous ethanol as solvents through precipitation method and hydrothermal method. The NiCo-LDH has a hollow nanoflower structure.

2. The hollow nanoflower NiCo-LDH according to claim 1, characterized in that: The size of the hollow nanoflower NiCo-LDH is 600-700nm, the wall of the hollow nanoflower structure has a secondary structure, the secondary structure is a layered structure composed of small hydrangeas, the size of the small hydrangeas is 100nm, and the primary unit of the small hydrangeas is an LDH flake.

3. A method for preparing hollow nanoflower NiCo-LDH, characterized in that The following steps are involved: Step 1, preparation of ZIF-67, first, dissolving Co(NO3)·6H2O in deionized water to obtain solution A, and at the same time, dissolving dimethylimidazole 2-MI, thiourea TU, hexadecyltrimethylammonium bromide CTAB and dimethyl sulfoxide DMSO in deionized water to obtain solution B, then mixing solution A and solution B, and reacting by stirring first and then standing, and after the reaction is completed, centrifuging and drying the obtained product to obtain ZIF-67; Step 2, preparation of hollow nanoflower NiCo-LDH, first, under certain conditions, the ZIF-67 and Ni(NO3)·6H2O obtained in step 1 are dissolved in anhydrous ethanol and stirred to obtain solution C, then, under certain conditions, solution C is subjected to a hydrothermal reaction, and after the reaction is completed, the obtained product is washed and dried to obtain hollow nanoflower HNF-NiCo-LDH.

4. The preparation method according to claim 3, characterized in that: In the step 1, the ratio of Co(NO3)·6H2O, 2-MI, TU, CTAB and DMSO satisfies 8g:17g:1g:0.02g:14mL; In the step 2, the mass ratio of ZIF-67 to Ni(NO3)·6H2O is 1:

11.

5. The preparation method according to claim 3, characterized in that: In the step 1, the conditions for stirring first and then standing are: the stirring time is 1 hour and the standing time is 6 hours.

6. The preparation method according to claim 3, characterized in that: In the step 2, the stirring condition is that the stirring time is 0.5-1h; in the step 2, the hydrothermal condition is that the hydrothermal temperature is 80° C. and the hydrothermal time is 6h.

7. The use of the hollow nanoflower NiCo-LDH as a supercapacitor electrode material according to claim 1, characterized in that: At a discharge current density of 1A -1 When the specific capacitance of HNF-NiCo-LDH-6 is 1538-1834 F g -1 .

Citation Information

Patent Citations

  • Preparation method of hollow hydrangea flower cluster magnetic nano composite structure

    CN110189881A

  • Preparation method and application of ZIF-67 selenide

    CN111978556A

  • Cr2O3-loaded porous metal organic framework material for catalytic synthesis of azelaic acid

    CN116943737A

  • ZIF-67 / NiCoMo-LDH / NF composite structure material and preparation method and application thereof

    CN118553542A

  • Reinforced Adsorbent Fibers and Applications

    US20240269603A1